PUBLIC VALUE PEDAGANG DALAM PENGGUNAAN E-RETRIBUSI DI PASAR TRADISIONAL BANGETAYU KOTA SEMARANG - Nur Afifah, Milla; Hanani, Retna; Sunu Astuti, Retno (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The city of Semarang implemented electronic e-retribusion system in 2018. E- Retributions were carried out with the aim of increasing the efficiency and reducing the costs of retribusion colletion . However, there has been a decline in E-Retribution income at Bangetayu Market, one of which is due to changes in the form of public services from previously manual system to automatic through the use of E-Retribution. The aim of the research is to determine the public value with Bangetayu Market traders in using e-retribusi in add the research finds.. Apart from that, to find out the factors that encourage and hinder traders in using e-retribution at Bangetayu Market.. In this research, the researcher used a qualitative descriptive method using data collection techniques in the form of interviews, observation and literature study. Based on data obtained from research results, Bangetayu Market traders do not accept e-retribution because traders consider e-retribution to be less profitable for traders, less suitable for use, traders are less happy in using it, traders have difficulty using e-retribution. However, the existence of levies can increase traders' trust in officers and increase traders' knowledge in using e-money.